A Study on Race Condition & Dynamic Data Race Detection Techniques - Dubey, Mithilesh Kumar; Lowe, Devesh; Galhotra, Bhavna (International Journal of Computer Sciences and Engineering, 2019)
Multithreaded programming has always presented a problem of race conditions which is one of the most common programming errors. If not handled properly, can lead to bugs with the potential to crash a system. A lot of work has been done in the past for detection of data races with a view to minimise the losses. Datarace can be detected at compile time (static race detection) and at runtime (dynamic race detection). This paper presents a study to understand the concept of parallel programming, race condition, semaphore, synchronization. We have also put in a detailed view on various techniques developed so far for dynamic data race detection.